Integrating an exercise program into opioid agonist therapy: a pilot study on feasibility, fitness improvements, and participation challenges - Einar Furulund; Siv-Elin Leirvåg Carlsen; Silvia Eiken Alpers; Jørn Henrik Vold; Karl Trygve Druckrey-Fiskaaen; Tesfaye Madebo; Sindre M. Dyrstad; Torgeir Gilje Lid; Lars Thore Fadnes (Addiction Science & Clinical Practice)
Abstract Background People receiving opioid agonist therapy (OAT) face high risk of comorbidities, including cardiovascular and mental health disorders. Integrating exercise programs with OAT may reduce health disparities and improve well-being. This study explored the feasibility and preliminary effects of an integrated exercise program. Method This multicentre, mixed-methods pilot study was conducted in Western Norway, recruiting 22 participants receiving OAT from three outpatient clinics. The six-week, group-based exercise program focused on high-intensity endurance and strength training. Changes in aerobic fitness (4-minut step test), psychological distress (10-item Hopkins Symptom Checklist, SCL-10), fatigue (3-items Fatigue Severity Scale, FSS-3), lung function (spirometry), and respiratory symptoms (modified Medical Research Council Dyspnea Scale, mMRC) were assessed, while qualitative interviews provided insights into intervention feasibility. Results Pre- and post-test assessments indicated improvements in aerobic fitness, as measured by the 4-minute step test, with a pre-test mean of 89.4 (SD: 24.7) and a post-test mean of 103.1 (SD: 31.3) step-cycles, despite a modest attendance rate of 28%. Psychological distress, evaluated using the SCL-10, increased in score from 1.85 (SD: 0.66) to 2.03 (SD: 0.59). Fatigue also increased slightly Fss-3: 4.44 (SD:2.38) to 5.07 (SD:2.01), while respiratory symptoms using mMRC, lung capacity with FVC, and expiratory volume FEV1 remained stable. Qualitative findings were categorized into three main themes: (1) The clinic as an arena for physical activity, (2) a modest move with a substantial benefit for participants, (3) challenges and adjustments to the intervention. Participants reported that exercising in connection with the OAT clinic promoted a sense of care and support from clinicians. Many experienced increased self-confidence and social engagement, though attendance was affected by health issues, fluctuating motivation, and logistical challenges. Conclusion This pilot study suggests that integrating structured exercise into OAT can be feasible and improve aerobic fitness. However, increased psychological distress and fatigue might indicate the need for additional support. The low attendance rate highlights engagement challenges, emphasizing the need for tailored strategies to enhance participation. Future research should focus on optimizing intervention design to improve attendance and enhance physical and psychological outcomes for individuals in OAT.